2021
DOI: 10.11648/j.ijbbmb.20210601.13
|View full text |Cite
|
Sign up to set email alerts
|

Yield Stability Analysis of Elite Irish Potato (<i>Solanum tuberosum </i>L.) Varieties in Western Ethiopia

Abstract: Potato is one of the most important horticultural crops widely grown in mid and high lands of Ethiopia. Several potato genotypes has been introduced and tested in different parts of western Ethiopia. However, the stability and performance of these genotypes under different parts of the regions were not yet assessed. Therefore, the objective of this study was to determine the effect of genotype, environment and their interaction for tuber yield and identify stable potato genotypes for possible recommendation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…A study on stability analysis for nine genotypes of Elite Irish Potato (Solanum tuberosum L.) was con ducted in western Ethiopia. The study r evealed CIP384321.30 as the stable genotype for the region on the basis of the mean tuber yield, regression slope identified, and GGE biplot (Fufa and Fufa, 2021). Similar conclusions were drawn from our present study in which stable germplasm was identified across the studied environments along with individual stable germplasm f o r e a c h e n v i r o n m e n t w i t h t h e w h i c h -w o n -w h e r e pattern approach.…”
Section: Discussionmentioning
confidence: 94%
“…A study on stability analysis for nine genotypes of Elite Irish Potato (Solanum tuberosum L.) was con ducted in western Ethiopia. The study r evealed CIP384321.30 as the stable genotype for the region on the basis of the mean tuber yield, regression slope identified, and GGE biplot (Fufa and Fufa, 2021). Similar conclusions were drawn from our present study in which stable germplasm was identified across the studied environments along with individual stable germplasm f o r e a c h e n v i r o n m e n t w i t h t h e w h i c h -w o n -w h e r e pattern approach.…”
Section: Discussionmentioning
confidence: 94%
“…Any cultivars with a significant  2  are regarded as unstable. This stability analysis on potato has been used for interpreting results of multi-environment trials and selecting superior breeding clones and suitable cultivars, for example, in Brazil (Souza Lambert et al 2006), Canada (Tai and Young 1972), Ethiopia (Fufa and Fufa 2021), India (Raja et al 2018), Iran (Hassanpanah et al 2008), Kenya (Lung'Aho et al 1998, Naawe 2020, Latvia (Skrabule et al 2015), Perú (Ortiz et al 1991), Türkiye (Pehluvan et al 2006, Uganda (Kakuhenzire et al 2004) and USA (Mackenzie et al 1976, Darmo andPeloquin 1990); while the CV facilitated identifying promising potato bred-germplasm in Iran under water deficit and potassium humate (Hassanpanah et al 2008), or in Kenya (Naawe 2020) and in Poland (Przystalski and Lenartowicz 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the AMMI modeling facilitates delineating mega-environments and improves trial accuracy. AMMI has been used for analyzing multi-environment potato yield trials in Brazil (Queiroz de Souza 2007), Croatia (Mijić et al 2019), Ethiopia (Worku et al 2018, Fufa andFufa 2021), Iran Azimi 2010, Mohammadnia et al 2021), Kenya (Naawe 2020), Korea (Kim et al 2017), Rwanda (Placide et al 2022, and Uganda (Mulema et al 2008). Its modeling, particularly when using the ensuing biplots, led to identifying breeding clones for further cultivar registration and suitable cultivar for respective sites in the target population of environments.…”
Section: Introductionmentioning
confidence: 99%